A (falta de) capacidade distintiva dos nomes de domínio à luz do ordenamento jurídico português - Azevedo de Amorim, Ana Clara (Law, State and Telecommunications Review, 2025)
[Purpose] The text addresses the admissibility of registering domain names without distinctiveness, in particular generic and descriptive expressions. In this way, it seeks to deepen the debate on the classification of domain names as atypical distinctive signs, helping to clarify the issue of exclusivity associated with it. [Methodology] Analysis of the Regras de Registo de Nomes de Domínio de .PT, as well as the relevant doctrine and case law on domain names. Comparison with the legal framework of trademarks and trade names, which are paradigmatic examples of typical distinctive signs. [Findings] The registration of domain names without distinctiveness constitutes a restriction on freedom of competition, contrary to the requirement of availability. It also encourages speculative and abusive behaviour, which may constitute unfair competition.